2011
DOI: 10.2337/db10-0778
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Adversely Affects Macrophages During Atherosclerotic Plaque Regression in Mice

Abstract: OBJECTIVEPatients with diabetes have increased cardiovascular risk. Atherosclerosis in these patients is often associated with increased plaque macrophages and dyslipidemia. We hypothesized that diabetic atherosclerosis involves processes that impair favorable effects of lipid reduction on plaque macrophages.RESEARCH DESIGN AND METHODSReversa mice are LDL receptor–deficient mice that develop atherosclerosis. Their elevated plasma LDL levels are lowered after conditional knockout of the gene encoding microsomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
132
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(160 citation statements)
references
References 44 publications
27
132
1
Order By: Relevance
“…In murine models, hyperglycaemia is associated with increased numbers of circulating monocytes -especially inflammatory LY6C + monocytes 179 -and polymorphonuclear cells (PMNs) 180 , which leads to their increased, proportional entry into plaques and consequent accelerated lesion progression. This seems to be replicated clinically: compared with individuals who have atherosclerosis alone, individuals with atherosclerosis and diabetes show impaired regression in response to cholesterolreducing therapies 181 , emphasizing the challenge of attempting to pharmacologically resolve clinical disease.…”
Section: Box 3 | Challenges With Translation Into Humansmentioning
confidence: 90%
“…In murine models, hyperglycaemia is associated with increased numbers of circulating monocytes -especially inflammatory LY6C + monocytes 179 -and polymorphonuclear cells (PMNs) 180 , which leads to their increased, proportional entry into plaques and consequent accelerated lesion progression. This seems to be replicated clinically: compared with individuals who have atherosclerosis alone, individuals with atherosclerosis and diabetes show impaired regression in response to cholesterolreducing therapies 181 , emphasizing the challenge of attempting to pharmacologically resolve clinical disease.…”
Section: Box 3 | Challenges With Translation Into Humansmentioning
confidence: 90%
“…As chronic hyperglycemia had been shown to promote myelopoiesis, increased numbers of neutrophils and monocytes were found in diabetic mice (31), which could result in an increase of their entry into inflammatory sites, leading to prolonged immune response and delayed lesion regression. In addition, tissue macrophages isolated from diabetic mice showed defective polarization into anti-inflammatory/tissue repairing M2 phenotypes (15,32), which would also lead to the persistence of tissue inflammation. Why was it not the case in our model?…”
Section: Liver Ischemia Reperfusion Injury In Diabetesmentioning
confidence: 99%
“…In vitro, macrophages can polarize toward either the M1 or M2 state by treatment with IFN-γ and LPS, or IL-4 and IL-13, respectively. Notably, in regressing atherosclerotic plaques, we have observed that there is reduced expression of classical inflammatory genes characteristic of M1 macrophages, such as monocyte chemoattractant protein-1 (MCP-1), TNF-α, and iNOS, coincident with increased expression of genes encoding markers of alternatively activated, tissueremodeling M2 macrophages, such as arginase 1 (ARG1), mannose receptor (MR, also known as CD206), and IL-10 in CD68 + cells (2,3,5,12,13). Importantly, the enrichment of plaque CD68 + cells with markers of the M2 phenotype, though initially discovered in the transplant model (5,12), has been subsequently found in several different models of atherosclerosis regression (2-4), suggesting this represents a signature of plaque regression.…”
Section: Introductionmentioning
confidence: 99%